XIVth YOUTH SYMPOSIUM ON EXPERIMENTAL SOLID MECHANICS - Editorial, Foreword (Acta Polytechnica CTU Proceedings)
The Youth Symposium on Experimental Solid Mechanics traditionally brings together young researchers and engineers, students and PhD students, who are actively involved in the experimental solids mechanics, theoretically and practically, in order to exchange their experience, to report on the present state-of-art as well as on running research projects, to discuss due questions and problems and to promote the cooperation among individuals as well as among institutions. The XIVth symposium continues both, the long tradition of this conference series and introduces novel elements. The combination of the experimental mechanics with modern numerical methods was focused. This year, participants from 12 countries attended the symposium. Based on their presentations, 19 papers were selected for the publication in this issue of Acta Polytechnica CTU Proceedings. Zoltan Major, Daniel Kytýř Editors Local organizing comittee: Zoltan Major Melinda Bozzay Petra Schiefermüller Johannes Sailer Judith Raab Scientific Comittee: Tadaharu Adachi (Toyohashi University of Technology) Otakar Bokůvka (University of Žilina) Lajos Borbás (Budapest University of Technology and Economics) Katia Casavola (Polytechnic Institute of Bari) Fulvio Chimisso (Federal University of Rio Grande) Anibal Cofone (University of Buenos Aires) Dan Constantinescu (Technical University of Bucharest) Josef Eberhardsteiner (Vienna University of Technology) Alessandro Freddi (University of Bologna) Patricia M. Frontini (University of Mar del Plata) Rita Kiss (Budapest University of Technology and Economics) Daniel Kytýř (Czech Technical University in Prague) Karl-Hans Laermann (University of Wüppertal) Evgenij V. Lomakin (Lomonosow University Moscow) Zoltán Major (Johannes Kepler University Linz) Antonio Martinez (Universitat Politecnica de Catalunya) Paweł Maslak (Wrocław University of Technology) Lluisa M. L. Maspoch (Universitat Politècnica de Catalunya) Giangiacomo Minak (University of Bologna) Giorgio Olmi (University of Bologna) Gerald Pinter (Montanuniversität Leoben) Milan Růžička (Czech Technical University in Prague) Damir Semenski (University of Zagreb) Marcus Schoßig (Merseburg University of Applied Sciences) Jürgen Vogel (University of Applied Sciences Zwickau) Klaus Vogel (Fraunhofer-Instituts für Elektronische Nanosysteme)